If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X-2=3X-3
We move all terms to the left:
X-2-(3X-3)=0
We get rid of parentheses
X-3X+3-2=0
We add all the numbers together, and all the variables
-2X+1=0
We move all terms containing X to the left, all other terms to the right
-2X=-1
X=-1/-2
X=1/2
| 7/x+5=5/6x-4 | | 5(x-1)+2(x+3)=0 | | 3(x+6)+2(x+3)=0 | | -x+5=-2x+6 | | 6t-3=12 | | 6x+8.06=3x+14 | | 8a+12=6a+14 | | -2(x-5)^2=36 | | -x+3=3x+9 | | -2/5w=6 | | 4x^2=-160 | | 3y^2-y=1 | | (4,5)m=-4/5 | | 15X-27=4x-6 | | 3x+7=-8+2x | | 5^2x+4=1/25^x+2 | | 6x−(7x−12)=101 | | 4z/10+3=-6 | | 15x-3(x-5)=3-15x+3 | | 5(3x-2)=9x+2 | | 1/x=2.22 | | 11x+15=3x-7 | | -1=w/8+4 | | x+4=10021 | | 3/5x+1/4=7/4 | | .6x+.25=1.75 | | 69=4w-11 | | -22=4x-2 | | x÷3+(2x+4)=2x÷15-6x+7÷30 | | p-27=836 | | 257=q-694 | | 5x+3÷(2)-7-4x÷(5)=-x-6÷(3) |